2020
DOI: 10.1111/jen.12839
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the susceptibility of raspberries to Drosophila suzukii oviposition

Abstract: Raspberry (Rubus idaeus L.) is an important fruit crop (Graham et al., 2004) and cultivated in most areas in the world (Strik, 2007). Raspberry fruits are grown for fresh fruit market or commercial processing including products like juice, dried or frozen fruit and puree and its leaves are known for an astringent flavour in herbal teas (Hanke & Flachowsky, 2017). The main producing world re

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…The skin resistance of grapevine berries was shown to be the determining factor in the number of eggs oviposited when compared to other fruit parameters [53]. Skin penetration resistance and other characteristics such as brix, pH, skin firmness, and coloration were not quantified in this study but have been shown to be major factors in the susceptibility of fruit to pest infestation [29,[54][55][56]. On average, it is established that the skin penetration resistance of a fruit is negatively correlated to D. suzukii oviposition levels and that fruit with higher pH and brix are more attractive to D. suzukii for oviposition and development [20,29,46,55,[57][58][59].…”
Section: Discussionmentioning
confidence: 79%
“…The skin resistance of grapevine berries was shown to be the determining factor in the number of eggs oviposited when compared to other fruit parameters [53]. Skin penetration resistance and other characteristics such as brix, pH, skin firmness, and coloration were not quantified in this study but have been shown to be major factors in the susceptibility of fruit to pest infestation [29,[54][55][56]. On average, it is established that the skin penetration resistance of a fruit is negatively correlated to D. suzukii oviposition levels and that fruit with higher pH and brix are more attractive to D. suzukii for oviposition and development [20,29,46,55,[57][58][59].…”
Section: Discussionmentioning
confidence: 79%
“…Red-and soft-fruited hosts in the section Myrtillus, especially Hawaiian and Tahitian genotypes, were the most susceptible to fly attack. However, larger hexaploid fruit appear to also exhibit resistance perhaps due to their thicker epidermis, as was the case in a comparative host study of raspberry genotypes infested by D. suzukii (Wöhner et al 2021). Diploid fruits of some genotypes were sufficiently small, tart, sweet, and firm to thwart entirely D. suzukii feeding and oviposition.…”
Section: Discussionmentioning
confidence: 91%
“…These differences in cultivar susceptibility were attributed to variation in fruit firmness and penetration force between cultivars, with fewer eggs laid in firmer fruit [ 45 ]. The role of fruit firmness was corroborated in laboratory comparisons of raspberry cultivars [ 46 ]. Additional interactions between the fruit’s chemical and physical properties may also influence susceptibility.…”
Section: Cultural Control Tacticsmentioning
confidence: 96%
“…Ripe fruit is more susceptible to D. suzukii than unripe fruit [ 14 , 43 , 44 ]. Fruit softens and becomes sweeter as it ripens, and D. suzukii oviposition and larval development are positively correlated with °Brix (soluble sugars) and negatively correlated with fruit firmness [ 14 , 45 , 46 ]. These characteristics vary across crop types and varieties, and are also influenced by environment and production practices [ 47 , 48 ].…”
Section: Cultural Control Tacticsmentioning
confidence: 99%